2023
DOI: 10.1021/acsami.3c02874
|View full text |Cite
|
Sign up to set email alerts
|

Nanophase-Separated Copper–Zirconia Composites for Bifunctional Electrochemical CO2 Conversion to Formic Acid

Abstract: A copper–zirconia composite having an evenly distributed lamellar texture, Cu#ZrO2, was synthesized by promoting nanophase separation of the Cu51Zr14 alloy precursor in a mixture of carbon monoxide (CO) and oxygen (O2). High-resolution electron microscopy revealed that the material consists of interchangeable Cu and t-ZrO2 phases with an average thickness of 5 nm. Cu#ZrO2 exhibited enhanced selectivity toward the generation of formic acid (HCOOH) by electrochemical reduction of carbon dioxide (CO2) in aqueous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…[12][13][14] It was demonstrated that MONs having extended nanotextures can spontaneously emerge out of precursor alloys that consist of highly oxyphilic metals, such as early d-metals and lanthanides. [15][16][17] When subjected to an atmosphere containing oxygen (O 2 ), such precursor alloys are dissociated into metal and oxides as a result of the oxyphilic metal species being selectively converted into oxides. The infusion of oxygen atoms from the surface into the bulk of the precursor alloy develops a phase-connected MON comprising a nanometre-thick, interconnected network of metal and oxide (i.e., nanophase separation).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] It was demonstrated that MONs having extended nanotextures can spontaneously emerge out of precursor alloys that consist of highly oxyphilic metals, such as early d-metals and lanthanides. [15][16][17] When subjected to an atmosphere containing oxygen (O 2 ), such precursor alloys are dissociated into metal and oxides as a result of the oxyphilic metal species being selectively converted into oxides. The infusion of oxygen atoms from the surface into the bulk of the precursor alloy develops a phase-connected MON comprising a nanometre-thick, interconnected network of metal and oxide (i.e., nanophase separation).…”
Section: Introductionmentioning
confidence: 99%
“…The infusion of oxygen atoms from the surface into the bulk of the precursor alloy develops a phase-connected MON comprising a nanometre-thick, interconnected network of metal and oxide (i.e., nanophase separation). 16 The interconnected metal-oxide network in the MON leads to superior transport performances due to the spatially connected pathways of metal and oxide phases for electronic and ionic transport, respectively. [18][19][20] The phase-connected MON materials are, despite the inherent priority of spatial connectedness of material phases, still precluded from wide use in batteries or fuel cells due to the lack of a guiding principle to tune their phase texture toward maximized performances.…”
Section: Introductionmentioning
confidence: 99%
“…The CuO–CeO 2 catalyst exhibits an ethylene faradaic efficiency of 50% due to the long-term preservation of Cu + . 39 Other metal or metal oxides with the ability to regulate the electronic structure of Cu species, such as Al, 40 Zn, 41 SiO x 42 and ZrO 2 , 43,44 have also been reported to construct heterogeneous catalysts to improve the thermocatalytic or electrocatalytic multi-carbon selectivity for Cu-based catalysts. However, a facile but efficient strategy to stabilize Cu + to obtain high efficiency for C 2+ production in a wide potential window as well as clarify the deep mechanism are still at the core of the electrochemical CO 2 RR.…”
Section: Introductionmentioning
confidence: 99%